Right bundle branch pacing: Criteria, characteristics, and outcomes - Jastrzębski, Marek; Kiełbasa, Grzegorz; Moskal, Paweł; Bednarek, Agnieszka; Rajzer, Marek; Curila, Karol; Burri, Haran; Vijayaraman, Pugazhendhi (Heart rhythm, 2023)
BACKGROUND: Targets for right-sided conduction system pacing (CSP) include His bundle and right bundle branch. Electrocardiographic patterns, diagnostic criteria, and outcomes of right bundle branch pacing (RBBP) are not known. OBJECTIVE: Our aims were to delineate electrocardiographic and electrophysiological characteristics of RBBP and to compare outcomes between RBBP and His bundle pacing (HBP). METHODS: Patients with confirmed right CSP were divided according to the conduction system potential to QRS complex interval at the pacing lead implantation site. Six hypothesized RBBP criteria as well as pacing parameters, echocardiographic outcomes, and all-cause mortality were analyzed. RESULTS: All analyzed criteria discriminated between HBP and RBBP: double QRS complex transition during the threshold test, selective paced QRS complex different from conducted QRS complex, stimulus to selective-QRS complex > potential-QRS complex, small increase in V6 R-wave peak time (V6RWPT) during QRS complex transition, equal capture thresholds of CSP and myocardium, and stimulus-V6RWPT > potential-V6RWPT (adopted as the diagnostic standard). According to the last criterion, RBBP was observed in 19.2% of patients (64 of 326) who had been targeted for HBP, present mainly among patients with potential to QRS complex interval <35 ms (90.6% [48 of 53]) and occasionally among the remaining patients (5.6% [16 of 273]). RBBP was characterized by longer QRS complex (by 10.5 ms), longer V6RWPT (by 11.6 ms), and better sensing (by 2.6 mV) compared with HBP. During a median follow-up duration of 29 months, no differences in capture threshold, echocardiographic outcomes, or mortality were found. CONCLUSION: RBBP has distinct features that separate it from HBP and is observed in approximately a fifth of patients in whom HBP is intended.
Keywords: Humans; Capture criteria; Heart Conduction System; Right bundle branch pacing; echokardiografie; nemoci převodního systému srdečního; Electrocardiography; Echocardiography; Cardiac Conduction System Disease; Conduction system pacing; His bundle pacing; výsledek terapie; Cardiac Pacing, Artificial; převodní systém srdeční; lidé; ECG; Treatment Outcome; Bundle of His; kardiostimulace umělá; Hisův svazek; elektrokardiografie